Notes on the survey of Islamic Archaeological sites in South-Eastern Wallo (Ethiopia) - Deresse Ayenachew; Assrat Assefa (Revue des Mondes Musulmans et de la Méditerranée)
This paper is an account of an archaeological survey trip to the Islamic sites in South-Eastern Wallo in Ethiopia, conducted in July-August 2012. The surveyed area is located in the northern part of the Ifāt region where a Franco-Ethiopian team identified, between 2006 and 2010, several ruined Islamic urban 14th and 15th century sites. Specifically, the surveyed area was the crossroads of long-distance trade routes in the southern part of northern Ethiopia for centuries, around the trade center and center for Islamic education of Dawway. The surveys identified 6 ancient mosques, some of which can be architecturally related to the medieval sites of Ifāt, others being traces of the re-Islamization of the region in the 18th and 19th centuries. These mosques of different styles, as well as the two burial sites visited, invite further historical and archaeological research on the Islamic cultures of this region, which should provide important evidence of medieval Muslim settlements, and of its re-Islamization in more recent times.